Orientation to Mobility, Socialization, and Communication Android Apps to Help Visually Impaired Students Understand the State University of Surabaya (UNESA) Campus Environment - Andajani, Sri Joeda; Sartinah, Endang Pudjiastuti; Sumbawati, Meini Sondang (Journal of ICSAR, 2023)
UNESA is a national leader in education development. This is consistent with UNESA’s vision of achieving educational excellence. This realization is consistent with UNESA’s primary competency and capacity as a disabled-friendly campus, with one visually-impaired student. The goal of this research is to describe the outcomes of creating an Android application with a social mobility and communication focus to help students with visual impairments understand the UNESA campus environment. The product of this development research takes the form of an android application with a focus on social mobility and communication. Realization of product design, namely: 1) android application program packaged in mobile phones, 2) practical guide to access the outdoor environment on the way to various places in the UNESA Lidah Wetan and Ketintang campus environment with braille writing and writing alert, 2) cooperative form of think pair share type, 3) authentic assessment tool as a successful use of android applications in social orientation and communication mobility. The products created will be used by all visually impaired students who wish to visit the UNESA campuses in Lidah Wetan and Ketintang. UNESA’s inclusive campus is a place for all disabled people who want to continue their education, including the visually impaired who require environmental mobility facilities.